Deceased kidney donor cystatin C and subsequent recipient measured glomerular filtration rate at one year after transplantation - Isabelle J. C. Dielwart; Daan Kremer; Tim J. Knobbe; Dion Groothof; Henri G. D. Leuvenink; Jenny E. Kootstra-Ros; Martin H. de Borst; Marco van Londen; Jan-Stephan F. Sanders; Robert A. Pol; Stephan J. L. Bakker (PLoS ONE, 2026)
Background Deceased donor kidney selection is largely determined by creatinine-based kidney function estimation. However, muscle wasting is common in potential donors and affects the accuracy of creatinine-based kidney function assessment. Cystatin C could serve as a muscle-mass independent alternative for this purpose. The primary aim of this study was to evaluate the associations of donor creatinine and cystatin C with recipient measured glomerular filtration (mGFR) at one year after transplantation. Methods Using data from the prospective TransplantLines study, multivariable linear regression analyses were performed to examine the associations of donor plasma creatinine and cystatin C with recipient I 125 -iothalamate mGFR. Results Donor plasma creatinine and cystatin C data were available for 96 donor-recipient pairs. Median pre-donation creatinine and cystatin C concentrations were 56.0 [49.5–71.0] µmol/L and 0.63 [0.50–0.82] mg/L, respectively. Recipient mGFR data at one year after transplantation were available in 55 kidney transplant recipients. Mean recipient mGFR was 52.1 ± 17.0 ml/min. Donor plasma creatinine was not associated with recipient mGFR (st. β −0.19, 95% CI [−0.48 to 0.10], p = 0.21), while donor cystatin C was significantly associated with recipient graft function (st. β −0.52, [−0.83 to −0.21], p = 0.002). The association of cystatin C and recipient mGFR remained materially unchanged after adjustment for potential confounders. Conclusion In deceased kidney donors, donor plasma creatinine is not associated with recipient mGFR, whereas donor cystatin is associated. Addition of cystatin C to the assessment of deceased kidney donors may provide additional information in difficult cases and improve the accuracy of deceased kidney donor selection.